KAJIAN DOSIS PUPUK KANDANG SAPI DAN ELISITOR BIOSAKA TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Ardha Ardha; Siti Wulandari; Rosmalinda Rosmalinda; Ari Priyanto; Ikhsan Prasetya Indra (Journal of Agro Plantation (JAP), 2025)
Cocoa plants (Theobroma cacao L.) are one of the main commodities that are superior in the plantation industry which has an important role for the Indonesian economy. This study aims to determine the effect of the dose of cow manure and biosaccate elicitor on the growth of cocoa seedlings (Theobroma cacao L.). This research method uses a factorial Completely Randomized Design (CRD) with 9 treatment combinations and 3 replications so that 27 experimental units are obtained. The first factor is the dose of cow manure (K), namely: K1: 50 g cow manure / polybag, K2: 100 g cow manure / polybag, K3: 150 g cow manure / polybag. The second factor is the concentration of biosaccate elicitor (A), namely: A1: without biosaccate, A2: 45 mL / L biosaccate elicitor, A3: 60 mL / L biosaccate elicitor. The analysis used was analysis of variance (ANOVA), and continued with Duncan's Multiple Range Test (DMRT) analysis if the effect was significant at the 5% level. The results showed that the treatment of cow manure significantly affected the parameters of seedling height, number of leaves, stem diameter, leaf chlorophyll and dry weight of seedlings. The best dose of cow manure treatment was 150 g/polybag. The treatment of biosaccade elicitor significantly affected the parameters of seedling height, number of leaves and stem diameter. The best concentration of biosaccade treatment was 45 mL/L. The combination of cow manure and biosaccade elicitor showed no significant difference in all observation parameters.